Outcomes with MANTA Device for Large-Bore Access Closure after Transcatheter Aortic Valve Replacement: A Meta-Analysis. Issue 5 (2nd September 2020) - Megaly, Michael; Buda, Kevin G.; Brilakis, Emmanouil S.; Pershad, Ashish; Louka, Boshra; Saad, Marwan; Abdelaziz, Hesham K.; Anantha Narayanan, Mahesh; Syed, Mubbasher; Mentias, Amgad; Omer, Mohamed; Alexander, Jason; et al.
ABSTRACT: Background: Data comparing MANTA to other vascular closure devices (VCDs) after TAVR is limited. Methods: We performed a meta-analysis of all published studies reporting the outcomes of MANTA vs. other VCDs in TAVR patients. Outcomes included major and minor vascular complications, major and minor bleeding, VCD failure, blood transfusion, additional surgical or endovascular treatment, flow-limiting dissection, hematomas, pseudoaneurysm, change in hemoglobin, and length of stay (LOS). Definitions used were according to the "Valve Academic Research Consortium-2 consensus document" (VARC-2). Results: We included five observational studies with a total of 1, 410 patients (MANTA n = 601, other VCDs = 809). Three studies compared MANTA to the Proglide device (Abbot Vascular, CA, USA), and two studies compared MANTA to the Prostar XL device (Abbott Vascular, IL, USA). The prevalence of moderate to severe calcification was higher in the MANTA group (31% vs. 21%, p = 0.01) compared with other VCDs group. During the index hospitalization, there was no difference in all major or minor complications between MANTA and other VCDs. In a sensitivity analysis, comparing MANTA to Proglide, the risk of major and minor vascular complications, major and minor bleeding, and VCD failure was similar for both devices. Conclusion: In the TAVR population, although more used in calcified vessels, the safety profile and efficacy of the new collagen-based VCD, MANTA, is similar to currently available suture based VCD's Proglide and Prostar XL.